POSITIVE IMPACT OF SMART DEVICES AMONG HIGHER EDUCATION STUDENTS - RKAR. Kariapper, MS. Suhail Razeeth, P.Pirapuraj, ACM. Nafrees, AMF. Roshan (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Almost all have used smart devicesdespite geographical areas and countries. In detail, it is transparent that trendy smart devices rule the people, especially youngsters all around the world. Smart devices are being used in various domains despite the public of Sri Lanka; higher education is one of them. These smart devices are used for smart communication, sharing course material and knowledge, research purposes, group activities, e-learning, online tutorials, online assessments, and guest talks. This exploratory study approach was conducted to analyze the positive influence of smart devices in higher education among the undergraduates of the South Eastern University of Sri Lanka. This survey was carried out using a stratified sampling technique. The samples were collected from all the six faculties of the South Eastern University of Sri Lanka. Two hundred five responses have been collected out of 300 questionnaires. Descriptive statistics test and Chi-square test were applied for the statistical investigation purpose. As a result, most of the undergraduates (93.2%) use mobile phoneslike smart devices in academic activities. Though most of the undergraduates are using smart devices regularly, the awareness of the Learning Management System is low. The result shows that undergraduates strongly agree that smart devices are a convenient tool for academic purposes since smart devices make learning easy. The primary outcome of this study is that there is a significant relationship between the academic stream & faculty and the positive influence factors by using smart devices. In addition to this, there is a significant relationship between the stream & faculty and academic activities